The nature and meaning of the Directive 2013/34/EU on financial statements according to the CJ EU - Robert Kenyon MacGregor; Radka MacGregor Pelikánová (Central European Economic Journal (CEEJ), 2019)
The Directive 2013/34/EU is a fundamental part of European Union (EU) legislation harmonising the regime of financial and non-financial reporting throughout the entire EU, including reporting about corporate social responsibility (CSR). Inasmuch as its transposition deadline expired in 2015, it is possible and also highly elucidating to holistically study its nature and actual transposition. A related literature summing up, accompanied with a legislation and transposition review compiled via the EUR-Lex database, makes for a solid foundation for a holistic and critical exploration of the related case law of the ultimate judicial authority for the interpretation and application of the Directive 2013/34/EU, namely the Court of Justice of the EU (CJ EU). Researching this case law within the Curia database brings forth an interesting meta-analysis, refreshed by Socratic questioning, which reveals the approach of the CJ EU to the Directive 2013/34/EU. The hypothesis suggests that this case law of the CJ EU offers valuable and as-yet hitherto-neglected indices, signifiers about the EU conforming to the perception of the nature and meaning of the Directive 2013/34/EU. These indices could be pivotal for further improvement of the harmonized regime of financial and non-financial reporting, for the boosting of CSR and also for supporting European integration and its legitimacy.
Keywords: G38; K22; M14; O43; 330; Court of Justice of the EU; financial and non-financial reporting; Directive 2013/34/EU